2015
DOI: 10.1111/bcpt.12363
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Functional Assessment of 22 Newly Identified CYP2D6 Allelic Variants in the Chinese Population

Abstract: Cytochrome P450 2D6 (CYP2D6) is one of the most widely investigated CYPs related to genetic polymorphisms and is responsible for one-quarter of the currently used clinical drugs. We previously detected 22 novel, non-synonymous, mutated sites in the Chinese population, but nothing is known about the functional effects of these mutations in terms of specific CYP2D6 substrates. In this study, wild-type CYP2D6, two common allelic variants and 22 newly reported CYP2D6 isoforms were transiently expressed in 293FT ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
42
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(55 citation statements)
references
References 25 publications
9
42
4
Order By: Relevance
“…The results indicated that CYP2D6.10 exhibits the lowest catalytic activities on the metabolism of atomoxetine in vitro. These data were in accordance with most of the previous reported studies [15,16,17,18] and thus indicated that our CYP expression and metabolic activity analysis system was suitable for analyzing the catalytic activities of the other CYP2D6 allelic variants. For CYP2D6.10 allele, which occurs as the most common allele in the Chinese population, our investigation may provide guidance for the proper atomoxetine administration in the clinic.…”
Section: Discussionsupporting
confidence: 92%
“…The results indicated that CYP2D6.10 exhibits the lowest catalytic activities on the metabolism of atomoxetine in vitro. These data were in accordance with most of the previous reported studies [15,16,17,18] and thus indicated that our CYP expression and metabolic activity analysis system was suitable for analyzing the catalytic activities of the other CYP2D6 allelic variants. For CYP2D6.10 allele, which occurs as the most common allele in the Chinese population, our investigation may provide guidance for the proper atomoxetine administration in the clinic.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, some allelic variants showed a different trend. In our study, CYP2D6*90 exhibited the moderate clearance intrinsic value (43.15%), while the corresponding value was more than 60% in previous studies (Dai et al 2015;Cai et al 2016). And, CYP2D6*2, CYP2D6*87, CYP2D6*88, CYP2D6*95 showed the relative clearance intrinsic values 20.34, 9.53, 25.46, 25.06% classified into the seriously defective group, respectively, whereas in previous research ranged from 30% to 60% (Cai et al 2016) and even were above 60% (Dai et al 2015).…”
Section: Discussioncontrasting
confidence: 48%
“…In our study, CYP2D6*90 exhibited the moderate clearance intrinsic value (43.15%), while the corresponding value was more than 60% in previous studies (Dai et al 2015;Cai et al 2016). And, CYP2D6*2, CYP2D6*87, CYP2D6*88, CYP2D6*95 showed the relative clearance intrinsic values 20.34, 9.53, 25.46, 25.06% classified into the seriously defective group, respectively, whereas in previous research ranged from 30% to 60% (Cai et al 2016) and even were above 60% (Dai et al 2015). We speculated that the substrate-dependent intrinsic characteristics and metabolic path (hydroxylation and demethylation) of the CYP2D6 protein might be responsible for these results, as several groups have reported that a given CYP2D6 allelic variant can exhibit different catalytic activities towards different substrates in vitro and/or in vivo.…”
Section: Discussioncontrasting
confidence: 48%
See 2 more Smart Citations